Investigating the Role of the Ventromedial Prefrontal Cortex in the Assessment of Brands - Santos, Jose Paulo; Seixas, Daniela; Brandão, Sofia; Moutinho, Luiz (Frontiers in Neuroscience, 2011)
The ventromedial prefrontal cortex (vmPFC) is believed to be important in everyday preference judgments, processing emotions during decision-making. However, there is still controversy in the literature regarding the participation of the vmPFC. To further elucidate the contribution of the vmPFC in brand preference, we designed a functional magnetic resonance imaging (fMRI) study where 18 subjects assessed positive, indifferent, and fictitious brands. Also, both the period during and after the decision process were analyzed, hoping to unravel temporally the role of the vmPFC, using modeled and model-free fMRI analysis. Considering together the period before and after decision-making, there was activation of the vmPFC when comparing positive with indifferent or fictitious brands. However, when the decision-making period was separated from the moment after the response, and especially for positive brands, the vmPFC was more active after the choice than during the decision process itself, challenging some of the existing literature. The results of the present study support the notion that the vmPFC may be unimportant in the decision stage of brand preference, questioning theories that postulate that the vmPFC is in the origin of such a choice. Further studies are needed to investigate in detail why the vmPFC seems to be involved in brand preference only after the decision process.